IMPLEMENTASI PEMBELAJARAN SENI RUPA BERBASIS PROYEK DI SD NEGERI 101966 DESA PERTANGGUHAN - Chamelia Tasri Br Bangun; Elya Siska Anggraini (CV. ADIBA AISHA AMIRA, 2025)
Fine arts are included in the creativity part of production activities and work, in various activities there are many opportunities to develop children's fine arts creativity. This study aims to determine how the implementation of fine arts learning and how children create fine arts in elementary schools. The research method used is descriptive qualitative by conducting interviews with one of the teachers and practicing directly with students in order to find out the ability of students' creativity in working. The results showed that students at the school were quite proficient in working such as holding scissors, cutting neatly and pasting the cut results, children also had the ability to hold colour pencils well, but there were some students who were not yet proficient in cutting neatly and there were also some students who were not yet proficient in holding scissors